Back Cover Image, Volume 118, Number 9, September 2021. Issue 9 (24th August 2021) - Brechmann, Nils A.; Schwarz, Hubert; Eriksson, Per‐Olov; Eriksson, Kristofer; Shokri, Atefeh; Chotteau, Véronique
Abstract : The cover image is based on the Article Antibody capture process based on magnetic beads from very high cell density suspension by Nils A. Brechmann et al., https://doi.org/10.1002/bit.27776 .